Análise da atividade de trabalho dos necrotomistas - Silva, Frankleudo Luan de Lima (2014)
This dissertation aims at analyzing the work activity of necrotomists Department of Forensic Medicine (DMF) of a capital of the Brazilian Northeast. This goal unfolds in the following specific objectives: to know the organization and the working conditions of necrotomists; understand how stigma affects the lives of these professionals, detect traces of cooperation and solidarity manifested in their work activity; shed light about the risks present in such activity; know the strategies they develop to cope with death in their daily work; evidence if they feel recognized or not in his work. The study included six necrotomists that currently make up the cadre of that DMF, being all male, aged between 32 and 48 years and length of service ranging from four to 23 years. From a theoretical standpoint, the psychodynamics of work was the main approach used, although other clinical approaches to work have also been summoned. As for the method, this research is characterized by a field study of a qualitative nature, in which he sought to combine individual semi-structured interviews and systematic observations at necropsy room. For data analysis, the perspective adopted was content analysis by clipping issues. It was found that the actual organization of the work of necrotomists is marked by the existence of some common rules, built in exercise activity. Highlights the precariousness of working conditions, which represents a state investment incompatible with the demands of the organ. These conditions, combined with a representation of the negative social work necrotomists, which situates the list of those activities graded dirty work, disgusting, degrading, produce additional suffering, requiring these workers, in addition to physical exertion own this activity, psychic maneuvers to avoid slipping on the grounds of mental illness. It was found that the relationship of necrotomists with the various risks of their activity is mediated by individual and collective defensive strategies, without which the experience of suffering and fear would be much felt. It is emphasized, too, that work daily with violent deaths is a potentially destabilizing for these professionals, which arouses the need for building emotional defenses and elaborations subjective, urging the production of possible ways of experiencing the world of work and recreate itself as subject. It was noted, finally, that if on one hand the necrotomistas perceive their work recognized by the direction of DMF, by experts, by themselves, and less frequently by the families of the victims, on the other, the indifference of the State, expressed in underinvestment in technical conditions and low wages, shows a depreciation of the category.